Inhibition of Escherichia coli porphobilinogen synthase using analogs of postulated intermediates - Jarret, Caroline; Stauffer, Frédéric; Henz, Matthias E; Marty, Maurus; Lüönd, Rainer M; Bobálová, Janette; Schürmann, Peter; Neier, Reinhard (My University, 2000)
Background: Porphobilinogen synthase is the second enzyme involved in the biosynthesis of natural tetrapyrrolic compounds, and condenses two molecules of 5-aminolevulinic acid (ALA) through a nonsymmetrical pathway to form porphobilinogen. Each substrate is recognized individually at two different active site positions to be regioselectively introduced into the product. According to pulse-labeling experiments, the substrate forming the propionic acid sidechain of porphobilinogen is recognized first. Two different mechanisms for the first bond-forming step between the two substrates have been proposed. The first involves carbon–carbon bond formation (an aldol-type reaction) and the second carbon–nitrogen bond formation, leading to an iminium ion.
Results: With the help of kinetic studies, we determined the Michaelis constants for each substrate recognition site. These results explain the Michaelis–Menten behavior of substrate analog inhibitors — they act as competitive inhibitors. Under standard conditions, however, another set of inhibitors demonstrates uncompetitive, mixed, pure irreversible, slow-binding or even quasi-irreversible inhibition behavior.
Conclusions: Analysis of the different classes of inhibition behavior allowed us to make a correlation between the type of inhibition and a specific site of interaction. Analyzing the inhibition behavior of analogs of postulated intermediates strongly suggests that carbon–nitrogen bond formation occurs first.
Keywords: analogs of intermediates; inhibition studies; porphobilinogen synthase